Sistem Pendukung Keputusan Dalam Pemilihan Smartphone Terbaik Menggunakan Metode SAW - Fadilah Nuria Handayani; Intan Diasih; Vrisa Arana Salsabilla; Aprilia Pramudita (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The development of smartphone technology is becoming faster and more diverse, so consumers are often faced with problems in choosing smartphones that fit their needs and budgets. Decision Support System (DPS) can help consumers make the right decisions. The purpose of this research is to design the best smartphone decision support system using the Simple Additive Weighting (SAW) method. The SAW method is used to calculate the weight of smartphone attributes such as Price, Internal Memory, Smartphone Processing Performance and Speed, Camera Quality, Battery Capacity so that it can provide a solution to consumers in choosing smartphones according to their wishes and needs.